Etching of glass microchips with supercritical water. Issue 1 (5th November 2014) - Karásek, Pavel; Grym, Jakub; Roth, Michal; Planeta, Josef; Foret, František
Abstract : Supercritical water was tested as a versatile alternative to hydrogen fluoride-containing mixtures for etching of glass chips. Abstract : A novel method of etching channels in glass microchips with the most tunable solvent, water, was tested as an alternative to common hydrogen fluoride-containing etchants. The etching properties of water strongly depend on temperature and pressure, especially in the vicinity of the water critical point. The chips were etched at the subcritical, supercritical and critical temperature of water, and the resulting channel shape, width, depth and surface morphology were studied by scanning electron microscopy and 3D laser profilometry. Channels etched with the hot water were compared with the chips etched with standard hydrogen fluoride-containing solution. Depending on the water pressure and temperature, the silicate dissolved from the glass could be re-deposited on the channel surface. This interesting phenomenon is described together with the conditions necessary for its utilization. The results illustrate the versatility of pure water as a glass etching and surface morphing agent.